Narrative Research of Pedagogical Knowledge: A Sociocultural Perspective - Barrera Quiroga, Diego Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This research work reconstructs the experience of a teacher from Universidad de la Amazonia in Florencia Caquetá who through historization and narrative rehistorization reconstructed her teaching practices. The objective was to reconstruct the pedagogical knowledge based on her teaching experiences. The methodology used was historization and rehystorization through a dialogic work in all research developments. The sociocultural approach allowed the participants to focus on the different moments of the process. It was taken into account that for a practice to be understood as experience, it should be endowed with meaning through the constructed narrative, whether oral, corporal or written, because the primary form as experience takes meaning for the human being is through narratives. With this approach it was possible to answer the question: What do the narratives of teaching experiences experience of a teacher-director of the Spanish Language and Literature program of the Universidad de la Amazonia reveal about her pedagogical knowledge, and the learning and teaching of the language?